Performance Evaluation of Pervious Concrete Containing Glass Cullet and Glass Powder for Sustainable Construction - Afeez A. AWOLOKUN; Olusegun O. ALUKO; Temitope F. AWOLUSI; Mayowa A. OGIDI (FUDMA Journal of Engineering and Technology, 2026)
The utilization of waste materials in concrete production has gained significant attention due to its potential for sustainable construction and environmental conservation. This study evaluates the performance of pervious concrete incorporating glass cullet as partial replacement fo r coarse aggregate and glass powder as supplementary cementitious material. The experimental program investigated the physical and mechanical properties of the materials, as well as compressive strength, abrasion resistance, water absorption, and permeability of the produced mixes. Results indicate that up to 20% replacement of cement with glass powder improved compressive strength due to its pozzolanic activity, while glass cullet effectively replaced natural aggregates without adversely affecting workability. Pervious concrete with glass powder demonstrated reduced porosity and enhanced durability compared to control mixes. The findings suggest that integrating waste glass into pervious concrete not only improves mechanical and durability properties but also offers a sustainable solution for waste management and eco-friendly construction.
Keywords: Pervious concrete, glass cullet, glass powder, sustainable construction, compressive strength.